Mothers' experiences with neonatal care for low birth weight infants at home; a qualitative study in the Hohoe Municipality, Ghana - Schuler, Christina; Ntow, George Edward; Agbozo, Faith (Journal of pediatric nursing, 2019)
Purpose - To explore knowledge and beliefs of mothers on low birth weight (LBW), examine care provision at home and societal perceptions of LBW infants. - Design and methods - This qualitative study was conducted using hermeneutic phenomenological approach. Data of mothers who delivered LBW infants within 2years preceding the study were purposively extracted from the medical records of the Hohoe Municipality Hospital in Ghana. Twenty semi-structured interviews and three focus group discussions were conducted. A thematic analysis approach was performed using Atlas.ti. - Results - Mothers identified and described LBW babies based on frailty, size and activity levels. LBW recognition was easier for multiparous mothers by comparing with previous deliveries. LBW was linked to poor maternal diet, diseases during pregnancy and heavy workload. Although most mothers perceived their LBW babies as healthy irrespective of the size a few home-care practises differed. Smaller LBW infants were less likely to be socially accepted. In the first few weeks after birth the care of LBW infants is the core responsibility of grandmothers. Primiparous mothers and those whose infants were smaller (<2 kg) quested for more information and support on LBW newborn care at home. - Conclusion - There is a need to increase knowledge on risk factors and tackle lapses in the recognition and care of LBW infants. Counselling on recommended neonatal care should begin during antenatal care and reiterated during postnatal care. - Practical implication - Tailored in-depth and culturally-adapted counselling, discharge instructions and home-based postnatal visits targeted at LBW infants and their primary caregivers could improve care.